2022
DOI: 10.3758/s13423-022-02230-w
|View full text |Cite
|
Sign up to set email alerts
|

Evidence from partially valid cueing that words are processed serially

Abstract: There has been a longstanding debate about whether lexical and semantic processing of words is serial or parallel. We addressed this debate using partially valid cueing, where one of two words is cued. The cue was valid on 80% and invalid on the other 20% of the trials. The task was semantic categorization, and performance was measured by accuracy. The new feature was to limit attentional switching using a postmask of consonants that closely followed the presentation of words. We found a large effect of cueing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 48 publications
(70 reference statements)
1
2
0
Order By: Relevance
“…Altogether, these results are remarkably similar to previous dual-task experiments with semantic categorization and lexical decision tasks (White et al, 2018(White et al, , 2020White, Palmer, et al, 2019). See also Johnson et al (2022) for consistent evidence using a partially-valid cueing paradigm. Two prior dual-task studies also found performance consistent with the parallel model when the task was to judge the color of the letters (colored vs. gray) rather than word meaning (White et al, 2018(White et al, , 2020.…”
Section: Discussionsupporting
confidence: 87%
“…Altogether, these results are remarkably similar to previous dual-task experiments with semantic categorization and lexical decision tasks (White et al, 2018(White et al, , 2020White, Palmer, et al, 2019). See also Johnson et al (2022) for consistent evidence using a partially-valid cueing paradigm. Two prior dual-task studies also found performance consistent with the parallel model when the task was to judge the color of the letters (colored vs. gray) rather than word meaning (White et al, 2018(White et al, , 2020.…”
Section: Discussionsupporting
confidence: 87%
“…A related paradigm is called "partially-valid cueing," in which one of two stimulus locations is pre-cued as more likely to be task-relevant. One study using post-masked words found that when participants were asked to judge the semantic category of a word that appeared at the uncued (less attended) location, they performed no better than chance (Johnson et al, 2022). This is again consistent with the standard serial model for word recognition.…”
Section: Relation To the Wider Literature On Serial Versus Parallel W...supporting
confidence: 56%
“…We compare task performance to the predictions of serial and parallel processing. This complements other approaches that use dual-tasks or measure spatial attention effects (Johnson et al, 2022;White et al, 2018White et al, , 2020White, Palmer, et al, 2019).…”
mentioning
confidence: 77%
“…Altogether, these results are remarkably similar to previous dual-task experiments with semantic categorization and lexical decision tasks (White et al, 2018 , 2020 ; White, Palmer, et al, 2019b ). See also Johnson et al ( 2022 ) for consistent evidence using a partially valid cueing paradigm. Two prior dual-task studies also found performance consistent with the parallel model when the task was to judge the color of the letters (colored vs. gray) rather than word meaning (White et al, 2018 , 2020 ).…”
Section: Discussionmentioning
confidence: 95%